Challenges in preterm birth research: Ghanaian perspective. (1st September 2020) - Adu-Bonsaffoh, K.; Oppong, S.A.; Dassah, E.T.; Seffah, J.D.
Abstract: Preterm birth is highly prevalent in Ghana. It is a major public health concern because of the high burden as well as the associated immediate and long-term consequences including increased healthcare cost. Studies conducted in high-income countries may not be sufficiently generalizable in our context. Locally generated evidence-based interventions will be indispensable in improving the clinical management and prevention of preterm birth in the country. However, there are limited published literature on preterm birth and prematurity in the country. This review seeks to discuss the major challenges associated with preterm birth research in Ghana and proposes evidence-based strategies to improve biomedical and epidemiological research on preterm birth and prematurity. The limited high quality preterm birth research is partly attributable to a variety of challenges related to accurate gestational age estimation, research training, capacity and support including funding, efficient ethics committees, local and international collaboration as well as effective health management information systems. Other related challenges include unavailability of reliable internet connectivity, poor compensation for researchers and lack of conductive research environment. There is the need to expedite advocacy on implementation of practical interventions and strategies aimed at increasing high quality research in the area of preterm birth and prematurity in the country. A paradigm shift in preterm birth research with appropriate integration of concerted multidisciplinary research groups should be constituted to put basic science research to clinical practice as well as the prevention of preterm birth in the country. Highlights: Preterm birth is highly prevalent public health concern in Ghana. Evidence-based locally applicable recommendations are imperative. There is limited published research on preterm birth in the country. Practical challenges to preterm birth research are pervasive in the country.